THE EFFECT OF CAREER DEVELOPMENT ONEMPLOYEE PERFORMANCE AT PT. POS INDONESIA TASIKMALAYA BRANCH - Pipin Sukandi; Andini Dwi Harjanti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
To achieve the objectives of the company, the human resources need to be given a considerable boost to be motivated need to be rewarded with career development that can improve work performance of employees. One of the strategies that must be implemented by the management is planning and career development for all employees for their work in the company. For most employees the certainty of a career is very important because they will know the highest position they want to achieve, so they will be motivated and continue to improve our capacity and loyal to the company. The purpose of this study was to determine the influence of the Career Development Employee Performance at PT. Pos Indonesia Tasikmalaya branch. Population taken from employees of PT Pos Indonesia Branch Tasikmalaya, methods of sampling using Probability Sampling with saturated or census sampling in the sampling. Data processing is performed by the simple linear regression, correlation coefficient, coefficient of determination, hypothesis testing t. Based on the results of the calculation of Pearson Product Moment that the Career Development Job Performance can be said to be strong. From the calculation hypothesis test (t test), indicating that there is positive influence between the Career Development Job Performance at PT. Pos Indonesia. If the career development job performance is improved then will increase.